ANALISIS FAKTOR YANG MEMENGARUHI KECELAKAAN KERJA PADA PENGOPERASIAN CONTAINER CRANE DI PT X SURABAYA TAHUN 2013–2015 - Lilian Enggal Ekasari (The Indonesian Journal of Occupational Safety and Health, 2017)
Container crane for loading and unloading activities has hazard such as fall down, struck down, crushed or strangulated. It will induce accidents that result in economic and non-economic losses if not controlled. Therefore, this study aim to identify accidents in the operation of the container crane and factors that influence during the years 2013-2015.This research is descriptive research by describing the variables objectively. The data source of this research are reported of accidents in 2013-2015 and interviews related factors that affect accidents.The results showed that the number of accidents in the operation of the container crane continues to increase in a row from 2013-2015 year, that is 94, 69, 71. The value of average statistical that includes FR, SR and IR is 476.82, 0 and 110, 33. That value is high, although figures obtained SR is 0. For factors that influence the occurrence of accidents is unsafe worker behavior, surpervision systems, implementation of work instructions, maintenance and operation of the container crane related some programs that dysfunctin.Based on the results of this study concluded that the incidence and frequency of accidents is high although severity rate is 0. Causes of accidents are supervision system, implementation of work intruction unfavorable and dysfuction some programs related the operation of the container crane. Implementation of the program should be made to reduce the number of accidents in the operation of the container crane.Keywords:accident, crane, port